Analisis Rasio Keuangan untuk Mengukur Kinerja Keuangan - Setiowati, Lany; Kuntari, Yeni (Jurnal Ilmiah Aset, 2012)
The purpose of this research was to analyze the financial performance of Kawasan Industri Candi Semarang seen from finance ratio of the corporation. The analysis devices used were liquidty, solvability, profitability and activity ratio. Liquidity ratio as measured by current ratio showed the result of 3,62, quick ratio 2,77, Net working capital 2,61 it showed the company was above standard. Solvability ratio as measured from Debt to Asset Ratio showed the result of 0,23, Debt to Equity Ratio 0,29, Equity Multiplier 1,31 it showed a good condition in the investment. Profitability Ratio as measured from Gross Profit Margin showed the result of 0,87, net profit margin 0,11, return on asset 0,16, return on equity 0,20, productivity ratio 1,36 it showed that the company was good enough to generate profit in sales operational. Activity ratiomeasured by Receivable Turn Over showed the result of 9,14, the average revenue receivable 39,8, Total Asset Turn Over 1,36 it showed the company had good performance to support company activity.